Pulvinar sign in a case of anti-HU paraneoplastic encephalitis. Issue 6 (December 2016) - Gamache, Pierre-Luc; Gagnon, Maude-Marie; Savard, Martin; Émond, François
This article reports the case of a 68-year-old patient with anti-HU antibodies paraneoplastic encephalitis. The clinical manifestations were atypical and the paraclinical work-up, notably the magnetic resonance imaging (MRI) showing bilateral posterior thalamic hyperintensities (pulvinar sign), misleadingly pointed towards a variant Creutzfeld–Jakob disease. After presenting the case, the differential diagnosis of the pulvinar sign is discussed along with other important diagnostic considerations.